2022
DOI: 10.3390/ma15030825
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Conditions for Consolidation of Dissimilar Materials in Bimetal and Functional Graded Structures

Abstract: Functional Graded Structures and Functional Graded parts, made using dissimilar materials, are designed to provide specific properties to the final product. One of the most promising methods for manufacturing 3D Functional Graded objects is 3D laser cladding and/or direct energy deposition. However, the construction of graded and especially layered graded structures in the process of joining materials with different thermophysical properties under certain conditions is accompanied by the formation of cracks al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…In previous works [58,59], the authors of the article showed that the heat balance equation at the interface between two phases can serve as a basis for identifying the energy of discontinuity and identifying the conditions for the initiation of cracks, given the possible displacement of the phases relative to each other. Without taking into account heat transfers to the external environment, the heat balance equation near the phase boundary or an area with a large gradient in the change in chemical composition takes the following form:…”
Section: Theoretical Foundations Of the Research Methodsmentioning
confidence: 99%
“…In previous works [58,59], the authors of the article showed that the heat balance equation at the interface between two phases can serve as a basis for identifying the energy of discontinuity and identifying the conditions for the initiation of cracks, given the possible displacement of the phases relative to each other. Without taking into account heat transfers to the external environment, the heat balance equation near the phase boundary or an area with a large gradient in the change in chemical composition takes the following form:…”
Section: Theoretical Foundations Of the Research Methodsmentioning
confidence: 99%
“…As shown by the red circle in Figure 11, there were unmolten particles and micropores on the mirror surfaces, which not only degraded the surface quality but also reduced the surface densification. It is known that the mirrors used in visible and infrared systems have to be plated with a NiP layer to increase the surface roughness, but this may lead to bimetal effects because of the different thermal coefficients between NiP and the mirror blanks [15].…”
Section: Postprocessing For Surface Modificationmentioning
confidence: 99%